Calcium phosphate-alginate microspheres as enzyme delivery matrices - Ribeiro, Cristina C. (2017)
The present study concerns the preparation and initial characterisation of novel calcium titanium phosphate-alginate (CTPalginate) and hydroxyapatite-alginate (HAp-alginate) microspheres, which are intended to be used as enzyme delivery matrices and bone regeneration templates. Microspheres were prepared using different concentrations of polymer solution (1% and 3% w/v) and different ceramic-to-polymer solution ratios (0.1, 0.2 and 0.4 w/w). Ceramic powders were characterised using X-ray diffraction, laser granulometry, Brunauer, Emmel and Teller (BET) method for the determination of surface area, zeta potential and Fourier transform infrared spectroscopy (FT-IR). Alginate was characterised using high performance size exclusion chromatography. The methodology followed in this investigation enabled the preparation of homogeneous microspheres with a uniform size. Studies on the immobilisation and release of the therapeutic enzyme glucocerebrosidase, employed in the treatment of Gaucher disease, were also performed. The enzyme was incorporated into the ceramic-alginate matrix before gel formation in two different ways: preadsorbed onto the ceramic particles or dispersed in the polymeric matrix. The two strategies resulted in distinct release profiles. Slow release was obtained after adsorption of the enzyme to the ceramic powders, prior to preparation of the microspheres. An initial fast release was achieved when the enzyme and the ceramic particles were dispersed in the alginate solution before producing the microspheres. The latter profile is very similar to that of alginate microspheres. The different patterns of enzyme release increase the range of possible applications of the system investigated in this work.